Cotton Plantations in India: The Environmental and Social Challenges - Arun Sahay (Universitas Airlangga, 2019)
Cotton, one of the principal cash crops of India, contributes significantly to the country’s economy and foreign exchange earnings. Approximately 60 million people depend on cotton production and related industries for their livelihoods. Although India has the largest cotton plantation area, in terms of yield, it is far behind. Even though cotton occupies only five percent of India’s total cultivable land, approximately 50 percent of pesticides used in India are consumed by the cotton cultivation, causing environmental pollution and health hazard. The use of nitrogen-based fertilizers further increases the problem. Many social issues such as child labor, women labor, extremely small landholdings and unviable livelihoods are associated with cotton plantations. Recently, due to the norms set up by the textile importing countries, these issues have assumed great importance. This article, after giving a brief introduction to the cotton plantation sector in India, will deal with the environmental and social challenges of the cotton plantations.